The Beam Plasma Interactions Experiment: An Active Experiment Using Pulsed Electron Beams - Reeves, Geoffrey D.; Delzanno, Gian Luca; Fernandes, Philip A.; Yakymenko, Kateryna; Carlsten, Bruce E.; Lewellen, John W.; Holloway, Michael A.; Nguyen, Dinh C.; Pfaff, Robert F.; Farrell, William M.; Rowland, Douglas E.; Samara, Marilia; et al. (Frontiers in Astronomy and Space Sciences, 2020)
The 1970s and 1980s were heydays for using active electron beam experiments to probe some of the fundamental physical processes that occur throughout the heliosphere and in astrophysical contexts. Electron beam experiments were used to study spacecraft charging and spacecraft-plasma coupling; beam-plasma interaction physics; magnetic bounce and drift physics; auroral physics; wave generation; and military applications. While these experiments were enormously successful, they were also limited by the technologies that were available at that time. New advances in space instrumentation, data collection, and accelerator technologies enable a revolutionary new generation of active experiments using electron beams in space. In this paper we discuss such an experiment, the Beam Plasma Interactions Experiment (Beam PIE), a sounding rocket experiment designed to (a) advance HEMT-based RF linear accelerator electron accelerator technology for space applications and (b) study the production of whistler and X-mode waves by modulated electron beams.